2017
DOI: 10.1111/chd.12526
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular adaptation to the Fontan circulation

Abstract: Although medium-term survival following Fontan operations in the modern era has improved dramatically, late cardiovascular and extracardiac morbidity are common and are associated with impaired quality of life and premature late mortality. This serves as a reminder of the extraordinary adaptations required of the cardiovascular system when the systemic arterial, systemic venous and pulmonary circulations are placed in series coupled to a single ventricular pump. This article reviews the key features and princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 100 publications
1
25
0
Order By: Relevance
“…The architecture of functionally univentricular hearts differs from that of morphologically normal hearts [27]. Their myocardium seems to be inherently more fibrotic than that of normal hearts [28].…”
Section: Dominant Ventriclementioning
confidence: 95%
“…The architecture of functionally univentricular hearts differs from that of morphologically normal hearts [27]. Their myocardium seems to be inherently more fibrotic than that of normal hearts [28].…”
Section: Dominant Ventriclementioning
confidence: 95%
“…Many factors affect the development, including reduced blood flow, desaturation, collateral flow, lack of pulsatile flow, and absence of high blood flow and pressure during exercise. Also, the pulmonary circulation may have a progressive worsening over time leading to increased pulmonary vasculature resistance and, thus, a failing Fontan circulation (10,13,17,18).…”
Section: The Fontan Physiologymentioning
confidence: 99%
“…SVR and PVR), we could see that SVR was the main contributor to the effect, while there was only a relatively small change in PVR. This could reflect a vascular maladaptation of the systemic circulation to the chronic high systemic venous pressures [11] -the result of the circulations coupled in series.…”
Section: Discussionmentioning
confidence: 99%
“…While PVR is only a relatively small component of TVR, clinical and experimental studies have shown that it might have a large impact on cardiac output in the Fontan circulation [11]. This has formed the rationale behind PVD treatment.…”
Section: Discussionmentioning
confidence: 99%